Al-Ghazali Adab Curriculum as a Life Guide for The Alpha Generation - Rifqi Muhammad; Manja Manja; Patriana Patriana; Yusrain Yusrain (IAIN Ponorogo, 2022)
This research focuses on what is the adab in al-Ghazali's curriculum, and how can Imam al-Ghazali's curriculum of adab be a way of life for the alpha generation. This study uses a descriptive qualitative approach with the type of literature research and justification. The primary data source of this research is the book of Bidayatul Hidayah by Imam al-Ghazali. The results of the study found that the adab curriculum consisted of outward and inner adab. Here's the description; the etiquette of waking up from sleep, the etiquette of entering the toilet, wudhu etiquette, bathing etiquette, the etiquette of going and entering the mosque, the etiquette of self-preparation for salat, the etiquette wants to sleep, the etiquette of prayer, the etiquette of makmum, friday etiquette, the etiquette of fasting, the etiquette of guarding the eyes, the etiquette of guarding the ears, the etiquette of guarding the tongue, the etiquette of keeping the stomach, the etiquette of guarding the genitals, the etiquette of keeping two hands and two feet, abandoning hasad, abandon riya's nature, abandoning the nature of ujub, the etiquette with Allah SWT, student etiquette, the etiquette towards parents, the etiquette towards unknown persons, the etiquette towards close friends, the etiquette towards known people. Imam al-Ghazali justifies that if he practices the outward and inner adab, his faith will increase, and become a civilized person. So that the alpha generation who practice this inner and outer adab in their daily lives will become civilized individuals.